2007
DOI: 10.2500/ajr.2007.21.3077
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Papilloma with New Bone Formation: Report of Three Cases

Abstract: We propose that with regard to the three cases presented here, new bone formation may be associated with IP pathologically. We also believe that additional investigations are required to characterize the pathophysiological mechanisms involved in neoplasm-induced osteogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…Indeed, the ideal surgical management strategy of FS IP remains elusive to date. A variety of open, endoscopic, and combined approaches have been employed over the years to successfully extirpate FS IP, with mixed results 7–17. Several important observations stem from the present systematic review.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, the ideal surgical management strategy of FS IP remains elusive to date. A variety of open, endoscopic, and combined approaches have been employed over the years to successfully extirpate FS IP, with mixed results 7–17. Several important observations stem from the present systematic review.…”
Section: Discussionmentioning
confidence: 91%
“…A total of 13 studies with 57 patients reported sufficient individual data on patients treated for FS IP, defined as reporting the specific surgical approach and length of follow‐up for each patient 7–19. Studies were excluded that only reported aggregate outcomes, did not specify the surgical approach or length of follow‐up for each patient, or did not report whether recurrent or residual disease was identified during follow‐up.…”
Section: Methodsmentioning
confidence: 99%
“…Calcifications may be classified as entrapped bone structures or as primary tumoral calcifications. Essentially, entrapped bone is the bone fragment, which is enclosed within the tumor and erodes due to pressure atrophy whereas primary tumorous calcification is calcification created by the tumor itself; both may appear as calcifications on CT [13]. The histopathologic examination revealed no entrapped bone or primary tumor calcification in the current bone structure.…”
Section: Discussionmentioning
confidence: 99%
“…Osteogenesis in schwannoma is extremely rare, and only a few cases of schwannoma with osteogenesis in the internal auditory canal, lacrimal gland, spine, or other soft tissues have been reported [4–9]. New bone formation in nasal polyps has been demonstrated [10, 11], and bone formation in sinonasal inverted papilloma has been reported recently [12, 13]; however, to date, new bone formation in sinonasal schwannoma has not been reported. Here, we describe the first reported case of sinonasal schwannoma with new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Scans should be obtained in both axial and coronal planes. The CT appearance of inverted papilloma is variable and nonspecific [276, 286–290]. Unilateral opacification of the paranasal sinuses is typical CT findings papilloma [99].…”
Section: Work-up Investigationmentioning
confidence: 99%